Analysis of Tourism and Agrotourism Management in the Czech Republic and Austria - Eva Šimková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2014)
The paper discusses the importance of rural tourism and sustainable rural areas development. It highlights the role of tourism in dealing with problems of rural areas and agriculture sector in the Czech Republic. After theoretical description of a system approach to rural tourism development, the author continues by a practical part where she compares tourism and agrotourism management in the Czech Republic and Austria. Austria has been chosen as a representative of a state with developed tourism system and tourism management. Selected aspects of management systems are then compared and proposed for improvement in tourism/agrotourism. Critical key factor for successful development of activities in rural areas (therefore including agrotourism services) are then presented.